The roles of science, conflict and consensus in natural resource collaboration: lessons from an inactive collaborative group - Rudeen, Aleta, author; Fernandez-Gimenez, Maria, advisor; Thompson, Jessica Leigh, advisor; Meiman, Paul, committee member (Colorado State University. Libraries, 2009)
Collaboration is emerging as a potential solution to contentious natural resource management issues, but there is a need for deeper investigation of the causes of success and failure in these processes, and specifically the roles of consensus-based decision-making and the integration of science in collaboration. To address these gaps, I interviewed participants in an inactive collaborative group in the Intermountain West and analyzed their perceptions of science, success and consensus. This collaborative group did not reach a consensus decision with respect to its primary objective and also struggled with hurdles to the effective communication and integration of science in their decision-making process. I assessed participants' perceptions of the group's success, and explored the roles of conflict, communication and consensus decision-making in relation to the group's process and outcomes. I also investigated the various ways in which science was used to inform decisions and how the communication and integration of science affected the group's acceptance of science for decision-making. I found that the group experienced entrenched and intractable conflict, power inequalities, and hurdles to effectively incorporating science into decision-making. Participants were supportive of the use of scientific evidence for land management decisions in theory, but had difficulty applying science in practice. Major challenges to using science as a basis for collaborative decision-making were the group's inability to access information and lack of scientific information relevant to specific resources, sites and decision-making scales. Participants' acceptance of science varied with the perceived effectiveness and objectivity of individuals who communicated science to the group, and group members questioned whether science could inform decisions that were fundamentally value-based, such as whether a specific area should be designated as Wilderness or made available for energy development. Interviews revealed that collaboration improved communication and relationships among group members, and resulted in more comprehensive input on federal land management decisions than would not have occurred without collaboration. However, the unsuccessful attempt at consensus also decreased trust among some participants and may have discouraged them from participating in future collaborations. The apparently conflicting positive and negative outcomes of this collaborative group led to an apparent paradox whereby both the group's positive outcomes and its failure to achieve its goal are attributable to the group's commitment to consensus-based decision-making as the basis for its dialogue.
Keywords: Natural resources -- Management; Consensus (Social sciences)